Common Core Curriculum for Border Guards Basic Training in the European Union Countries - Andrii Balendr (Pedagogical Discourse, 2018)
The article reveals characteristics, the process of development and advantages of using of a Common Core Curriculum for the basic training of border guards (CCC) of the European Union countries. The Ukrainian Border Guard Service is also actively implementing this training program in its departmental educational and training institutions. The CCC consists of the General Chapter and modules «Air Border», «Land Border» and «Sea Border». The updated version of the 2018 CCC is aligned with the 4th and 5th levels of the Sectoral Qualifications Framework for border guarding and corresponds with the principles of the 4th and 5th levels European Qualifications Framework for Lifelong Learning. This training program facilitates interaction between the staff of the border services of the EU countries, offering a unified standard for basic training. This should help border guards perform their functions on a high professional level with respect for human dignity. The author analyzed the possibility of using this experience in order to implement it in the system of professional training of the personnel of the border guard agency of Ukraine. This should facilitate mobility and development of exchange programmes for the officers of border guard organizations, with the goal of providing common EU approaches to the organization of border security and introduction of common border guard standards across the EU. The CCC for border guards has also been considered regarding the possibility to utilize the experience of the leading EU border guard organisations in order to introduce it into the training system of the State Border Guard Service of Ukraine. The author indicates that the system of training of the personnel of the State Border Guard Service of Ukraine requires such an instrument for development of national border guard curricular for both educational and training purposes, and that presupposes further study of the border guard’s training system of the EU countries.